Online influential factors on hotel brand image and customers’ behavioral intention - Khoo, Jia Sheng; Neoh, Kah Wai; Tan, Hui Xuan; Teh , Oliver Qing-Sheng (2017)
Four online influential factors, namely personal eword-of-mouth, commercial eword-of-mouth, liking towards website, and perceived informativeness of online advertisements, we significant to the hotel brand image. The hotel brand image was further looked into and found that it had significance towards a customer‟s behavioural intention. The research took place in the Klang Valley area, with a total of 454 foreign tourist who participated in the survey questionnaire. The sample matrix was formed to segment respondents of different criteria and provided a more insightful data to conduct analyses with different sampling frame. In conclusion, the online influential factors were found to be significant to the hotel brand image. However, when broken down into respective hotel categories, it was found that budget hotels and 3-star hotels had no significance for the liking towards website and perceived informativeness of the online advertisements. Thus the hypotheses for the two construct were partially accepted. Overall, eword-of-mouth were highly significant in all categories of the hotels, and many implications, such as focusing on eword-of-mouth marketing, were suggested to businesses involved in the industry.